Seasonal variation of road runoff in cold climate - Westerlund, Camilla (Luleå tekniska universitet, Arkitektur och vatten, 2005)
The main objective of this thesis was to characterize and study the behaviour and transport of pollutants, i.e., suspended solids, particles and heavy metals, in road runoff from a small urban catchment during snowmelt and rainfall. The result will constitute a basis for essential considerations concerning the selection and design of environmental management practices and techniques in a cold climate. In regions with cold climate the urban drainage and highway runoff processes become much more complex, compared to temperate regions. The effects that runoff has on receiving waters seem to be particularly severe during snowmelt and rain-on-snow in cold climates. Therefore, climatic conditions should be taken into account in planning and design of BMPs and snow handling strategies. To increase the knowledge of seasonal variations of road runoff quantity and quality, measurements were carried out at a field site during melt and rain periods, year 2000 and 2001. The field site was a road with 7400 vehicles/day, in the central parts of Luleå in northern Sweden. Runoff samples were analysed for suspended solids (SS), particle-size distribution, total and dissolved heavy metals (Pb, Cu, Cd, Ni and Zn), pH, and conductivity. The results showed higher concentrations of SS, particles, and heavy metals for the melt period, as compared to the rain period, and the highest concentrations were found during the rain-on-snow events. The results indicated a flow dependent increase in the concentration of suspended solids during the melt period. The mass load for suspended solids, particles, and heavy metals was higher for the melt period than for the rain period. On the contrary, dissolved heavy metal loads were higher during the rain period. Metal elements during the melt period were more particulate bound as compared to the rain period characterised by a higher percentage of the dissolved fraction. During the melt period, investigated particle sizes and TSS were highly correlated with total concentrations of Cd, Cu, Ni, Pb, and ...